The Use of Neuroscientific Discoveries in Criminal and Civil Evidence Law - Magyar, Denis (Medicine, Law & Society, 2018)
The problem of objectification in criminal and civil evidence law is the basis of present work. Neuroscientific discoveries should be taken into account in evidentiary procedures when objectifying subjective facts. The first neuroscientific steps in objectifying pain and other subjective facts have already been made. The author outpoints certain limitations in the field of incorporation of neuroscientific discoveries into judicial procedures. He argues that some neuroscientific discoveries are already suitable for evidentiary purposes and their number will gradually increase. Neuroscience is looking forward to a gradual improvement of neuroimaging technologies that will increase the number of (reliable) discoveries applicable in evidence law. Neuroscientific discoveries are going to become an important part in objectification of subjective facts in criminal and civil procedures.Problem objektivizacije v kazenskem in civilnem dokaznem pravu predstavlja izhodišče predmetnega dela. Avtor zastopa stališče, da bi bilo koristno pri objektivizaciji subjektivnih dejstev uporabiti odkritja nevroznanosti. Ta je namreč že naredila prve korake na področju objektivizacije bolečine in drugih subjektivnih dejstev. Avtor opozarja tudi na omejitve, ki se lahko pojavijo pri uporabi nevroznanstvenih odkritij v sodnih postopkih. Zaključuje, da se lahko posamezna odkritja že uporabijo v dokazne namene in da se bo njihovo število še povečevalo. Nadaljnji razvoj bo namreč izboljšal nevroznanstvene metode, kar bo povečalo število (zanesljivih) odkritij v dokaznem pravu. S tem bodo nevroznanstvena odkritja postala pomemben del objektivizacije subjektivnih dejstev v kazenskih in civilnih postopkih.